Optimization of current density for nickel–chromium (Ni–Cr) alloy coating on copper: an experimental approach - Canute Sherwin; K. Raju; Prem Lata Meena; Richa Tyagi; Chandra Mohan (Discover Applied Sciences)
Abstract Conventional nickel/chromium electroplating can only meet a few new technological demands. Deposits with better properties must be tailor-made to meet present-day technology needs. This article is aimed to study the effect of plating parameters like current density, pulse current plating and plating time on the cathode current efficiency of Ni–Cr alloy plating on copper substrate. The primary purpose of this study is to determine the optimal plating parameters for plating nickel–chromium alloys by using experimental analysis. Parameters such as current density, plating time and type of current supply (DC/ Pulse) were considered for the analysis to determine the optimum plating parameters. The obtained optimal parameters were validated at four levels. First, coatings of Ni–Cr on copper substrates were developed, and outcomes were analysed. Secondly, the surface morphology of the coatings is examined using the Field Emission Scanning Electron Microscope (FESEM) technique. Thirdly, Energy Dispersive Spectroscopy (EDS) is performed on coated samples to evaluate the coating’s composition. Finally, X-ray Diffraction (XRD) is used to detect the phase of nickel–chromium deposits. XRD graphs demonstrate FCC structures for nickel and chromium with peaks 2θ angles around 45.5°, 52° and 77.5°. This shows a good crystalline layer of Ni–Cr alloy formed. SEM images indicate a homogeneous and dense morphology with fine grain size, representing effective alloying and uniform coating of the substrate. The results of this study indicate that coating parameters significantly influence the current efficiency during plating. The structure and nature of the coating depend on these parameters. The optimum plating parameters for Ni–Cr alloy plating on copper were found at a current density of 6 A dm−2 at pulse 3 and 10 min of plating time. New alloy electrodeposits with improved surface and mechanical properties are being explored. The study’s findings will help the automobile industry since it provides optimal plating parameters to get the alloy plating as a single-step coating.